Enhanced contact endoscopy for the detection of neoangiogenesis in tumors of the larynx and hypopharynx. (13th January 2015) - Puxeddu, Roberto; Sionis, Sara; Gerosa, Clara; Carta, Filippo
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Image‐enhanced endoscopy, such as narrow band imaging and the Storz Professional Image Enhancement System, have been increasingly used in patients with suspect lesions of the larynx and hypopharynx during preoperative and intraoperative assessment. Study Design In the present study, a contact endoscope was coupled with the systems of image‐enhanced endoscopy, as to precisely distinguish the peculiar neoangiogenetic changes in inflammation, and precancerous and cancerous lesions of the larynx and hypopharynx. Methods We performed a single‐blind study with this original approach of a series of 44 patients with different lesions of the larynx and hypopharynx. Results We observed five obvious vascular patterns matching the diagnosis in 41 patients out of 44, with accuracy in the differential diagnosis between normal tissue and hyperplasia versus mild dysplasia and carcinoma of 97.6%. Conclusions Enhanced contact endoscopy allows for predicting histologic changes of laryngeal and hypopharyngeal lesions from inflammation to cancer on based on fine evaluation of the neoangiogenetic changes of the chorion. This innovative procedure can be considered an important tool during diagnosis, treatment, and follow‐up of patients with precancer and cancer of the larynx and hypopharynx. Level of Evidence 1b. Laryngoscope, 125:1600–1606, 2015